Genetic and Immunological Pathogenesis of Atopic Dermatitis - Schuler, Charles F.; Tsoi, Lam C.; Billi, Allison C.; Harms, Paul W.; Weidinger, Stephan; Gudjonsson, Johann E. (Journal of investigative dermatology, 2024)
Type 2 immune–mediated diseases give a clear answer to the issue of nature (genetics) versus nurture (environment). Both genetics and environment play vital complementary roles in the development of atopic dermatitis (AD). As a key component of the atopic march, AD demonstrates the interactive nature of genetic and environmental contributions to atopy. From sequence variants in the epithelial barrier gene encoding FLG to the hygiene hypothesis, AD combines a broad array of contributions into a single syndrome. This review will focus on the genetic contribution to AD and where genetics facilitates the elicitation or enhancement of AD pathogenesis.